Evaluation of gamma irradiation and boiling treatment on antioxidant status in different spices. Issue 3 (9th September 2016) - Khatun, Afifa; Hossain, Afzal; Islam, Mahfuza; Munshi, Kamruzzaman; Akter, Afroza; Rahman, Badier; Huque, Roksana
Abstract: Three spice samples (garlic, ginger, and turmeric) were gamma‐irradiated at a dose of 0.05 and 0.1 kGy. The effects of irradiation treatment on the content of antioxidant markers (such as, total phenol, and flavonoid content, antioxidant activity, and reducing power) after boiling of fresh and gamma irradiated spices were investigated. Results indicated that the antioxidant quality of ginger has improved when treated with irradiation but irradiation treatment gradually decreased the antioxidant parameters with increasing dose in turmeric. For garlic, lower dose (0.05 kGy) was useful to retain antioxidant value after boiling than higher dose gamma radiation. In addition, boiling showed a significant loses of total phenol content and DPPH radical scavenging activity as well as other antioxidant markers were observed for fresh ginger and garlic. But fresh turmeric showed reverse phenomena upon boiling. The changes of bioactive compound upon irradiation and boiling might contribute to antioxidant activity of studied spices. Practical application: Gamma irradiation has been recognized as an effective method for inhibiting sprouting in rhizome spices along with improving safety of spices by inactivating food‐borne pathogens. In the present research, influence of gamma irradiation and boiling treatment on antioxidant status in different spices has been determined. Though irradiation has no positive effect on antioxidant parameters in boiled turmeric while irradiated ginger and garlic showed improvement of antioxidant markers in boiled sample. This result demonstrates that gamma irradiation could be a potential tool to improvement of antioxidant quality in cooked spices.